TRANSFORMASI PERPUSTAKAAN DALAM RANGKA MEWUJUDKAN LAYANAN PERPUSTAKAAN YANG INKLUSIF : STUDI KASUS DI PERPUSTAKAAN UMUM DAERAH KABUPATEN PULANG PISAU - Wahyu Deni Prasetyo; Dian Utami (Perpustakaan Nasional RI, 2020)
Library has a strategic role as a lifelong education whose can optimizing the services for all of people to developing personal potentional. The library also has a role as a leading sector to creating a literate society. Literate society in one side and an economic development in another side are two related variables. The regional government of Pulang Pisau Regency has colaborate with the National Library of Indonesia to reinforce the library by transforming library services based on social inclusion. Social inclusion based library are a library transformation that serves the information needs of all of the visitors. Social inclusion based library are also committed to meet the information needs of people with the information that can improve cognitive abilities and stimulating welfare improvement with library resources. This article discusses the transformation made by Pulau pisang regency public library to realize library services based on social inclusion.